Decentralization and macroeconomic instability: The importance of political and institutional factors - Abdul Jalil, Ahmad Zafarullah; Harun, Mukaramah; Che Mat, Siti Hadijah (World Business Institute (WBI), 2012)
The purpose of this paper is to examine the relationship between decentralization and macroeconomic stability.Even though there is a huge literature both theoretically and empirically on the impact of decentralization, only a few of them seems to be interested on the question of the link between decentralization and macroeconomic instability.It is thus our hope through this paper to shed more lights on the issue notably by looking at other dimensions of macroeconomic stability than the ones that are normally used in the literature and by examining other factors that might accentuate or diminish the effects of decentralization on macroeconomic instability.Evidence provided in this paper point to the fact that there is a negative relationship between certain variable of macroeconomic stability and decentralization.Our results also show that the impact of decentralization to be conditional on the level of perceived corruption and political institutions.It is found that the impact of decentralization on macroeconomic stability can be attenuated if corruption is high and the democracy is not being fully implemented.